The role of the initial material in breeding of the spring soft wheat varieties resistant to rust in Zauralye - L. T. Maltseva (Зерновое хозяйство России, 2018)
One of the factors limiting the growth of wheat productivity in Zauralye is the crop infection with leaf-stem diseases, which regularly occur three times in ten years, reducing the harvest on 5 to 30%. In 2015–2017 only two spring soft wheat varieties “Raduga” (Kurgan RIA) and “Uralosibirskaya” (SibRIA) (on 8–9% of the total area) out of 17 regionalized ones showed high tolerance to epiphytoty of brown and stem rust. The genetic collections of domestic and foreign origin have been used to develop new varieties. On the epiphytotic background there were identified varieties and samples with effective resistance genes. There has been conducted a target selection in the hybrid populations. There have been estimated morphologically aligned lines for reproduction. For the fast development of new varieties, there has been suggested stable and tolerant to the diseases, adaptive to local conditions initial material, namely the varieties “Sigma”, “Pamyati Leontieva”, “Boevchanka”, “Favorit”, “Novosibirskaya 31”, “Ingala”, “Sudarynia”, “Gerakl”, “Uralosibirskaya”, “Raduga” taken in the collection nursery; and the varieties and lines “Lutescens 120”, “Novosibirskaya 18”, “Rodnik”, “Lutescens 27-12”, “Lutescens 248/05-3”, “LD 25”, “Lutescens 34/08-19”, “Element 22”, “Lutescens 6/04-4” taken in the nursery of the Kazakh-Siberian Spring Wheat Improvement Network (KSSWIN). There have been identified 1340 highly productive lines out of 57 hybrid populations resistant to a wide range of brown rust types, including the virulent type Ug99. The 5 lines from the Siberian Breeding Nursery (SPCS) with complex resistance to brown and stem rust, powdery mildew and 6 varieties with the identified resistance genes to stem rust Sr31, Sr25 are of particular interest. The studied material is included in the breeding process.